Characterization of striga-resistant yellow-orange maize hybrids for bioactive, carbohydrate and pasting properties - Elemosho, A.O.; Irondi, E.A.; Alamu, Emmanuel Oladeji; Ajani, E.O.; Maziya-Dixon, Busie; Menkir, A. (Frontiers Media, 2020)
Understanding the bioactive constituents and physicochemical components in cereals can provide insights into their potential health benefits and food applications. This study evaluated some bioactive constituents, carbohydrate profiles and pasting properties of 16 Striga-resistant hybrids, with yellow-orange kernel color and semi-flint to flint kernel texture, grown in two replications at two field locations in Nigeria. Carotenoids were quantified using HPLC, while other analyses were carried out using standard laboratory methods. The ranges of major carotenoids (µg/g) across the two locations varied from 2.6 to 9.6 for lutein, from 2.1 to 9.7 for zeaxanthin, from 0.8 to 2.9 for β-cryptoxanthin, from 1.4 to 4.1 for β-carotene; with total xanthophylls and provitamin A carotenoids (pVAC) ranging from 5.4 to 17.1 and 1.4 to 4.1µg/g, respectively. Tannins content ranged from 2.1 to 7.3 mg/g, while phytate ranged from 0.4 to 7.1%. Starch, free sugar, amylose and amylopectin ranged from 40.1 to 88.9%, 1.09 to 6.5%, 15.0 to 34.1%, and 65.9 to 85.0%, respectively. Peak and final viscosities ranged from 57.8 to 114.9 and 120.3 to 261.6 Rapid Visco Units (RVU), respectively. Total xanthophylls, β-carotene, tannins, phytate, sugar, amylose and amylopectin levels, as well as peak and final viscosities, varied significantly (p < 0.05) across the hybrids. Amylose was significantly correlated (p< 0.05) with total xanthophylls, β-carotene, pVAC, phytate and pasting temperature (r = 0.3, 0.3, 0.4, 0.3, 0.3, respectively), but starch significantly correlated with tannins (r = 0.3). Hence, the Striga-resistant yellow-orange maize hybrids have a good combination of bioactive constituents, carbohydrate profile and pasting properties, which are partly influenced by hybrid.